Neumonía adquirida en la comunidad en paciente de sexo masculino de 55 años de edad. - Marín Ramírez, Solange Katherine (2020)
The current clinical case of a 55-year-old patient with community-acquired pneumonia, who came to the emergency for presenting a picture of hyperthermia, more headache, nausea, chills, cough with greenish expectoration, generalized discomfort, hypotensive, tachypneic, where the doctor on duty indicates his admission to the hospitalization area for better medical surveillance. Complementary examinations were performed on the patient, which helps to have a definitive diagnosis, which were the chest x-ray where infiltrations were found in the bases of both lung fields, in addition, there were diffusions, in the hemogram, leukocytosis was presented and oxygen desaturation. The treatments used in this type of patient were antibiotherapy to control the infection, inhalation therapy where drugs such as dexamethasone, ventolin, acetylcysteine were administered, which improved the patient's clinical picture, optimizing his lifestyle and improving hematosis. Low flow oxygen therapy was used with a nasal cannula at 2 liters per minute, improving patient saturation and correct gas exchange. The objective of this clinical case was to use the respiratory therapy technique in community-acquired pneumonia in a 55-year-old male patient, where it was possible to improve the clinical picture and stabilize the patient, including his symptom picture with the correct treatment. The patient was evaluated with the CURB-65 scale to assess the severity of the infection.